2022
DOI: 10.3389/fcell.2021.797341
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Comprehensive Prognostic Analysis of a Novel Chemokine-Related lncRNA Signature and Immune Landscape in Gastric Cancer

Abstract: Gastric cancer (GC) is a malignant tumor with poor survival outcomes. Immunotherapy can improve the prognosis of many cancers, including GC. However, in clinical practice, not all cancer patients are sensitive to immunotherapy. Therefore, it is essential to identify effective biomarkers for predicting the prognosis and immunotherapy sensitivity of GC. In recent years, chemokines have been widely reported to regulate the tumor microenvironment, especially the immune landscape. However, whether chemokine-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 86 publications
(103 reference statements)
1
4
0
Order By: Relevance
“…Next, the nomogram predicted survival time was almost consistent with the actual survival time. For example, Liang et al reported that the chemokine signature was identified for predicting overall survival in gastric cancer and showed good predictive efficiency, similar to our model [ 32 ]. In total, our risk model has sufficient efficiency and accuracy in predicting the survival outcomes of COAD patients.…”
Section: Discussionsupporting
confidence: 75%
“…Next, the nomogram predicted survival time was almost consistent with the actual survival time. For example, Liang et al reported that the chemokine signature was identified for predicting overall survival in gastric cancer and showed good predictive efficiency, similar to our model [ 32 ]. In total, our risk model has sufficient efficiency and accuracy in predicting the survival outcomes of COAD patients.…”
Section: Discussionsupporting
confidence: 75%
“…In immunotherapy, standard protocols emphasize immune checkpoint inhibitors, such as Keytruda and Opdivo, which target PD-1 or PD-L1 to activate the patient's immune system [36]. However, immunotherapy is not suitable for all patients, and the effectiveness of immunotherapy depends on PLOS ONE multiple factors, for example, the infiltrating of immune cells, the expression level of immune checkpoint genes, and somatic mutation status [37]. Therefore, it is crucial to develop effective immune characteristic models based on chromatin epigenetic regulator-related lncRNAs to improve the prognosis and assist clinicians and researchers in determining the appropriate immunotherapy approach.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of TMB are also correlated with the prognosis of GC patients. The increasing TMB level indicates a good prognosis of GC patients [ 22 24 ]. In addition, TMB could be used to predict the therapy response of patients to immunotherapy in multiple cancer types [ 25 27 ].…”
Section: Discussionmentioning
confidence: 99%